Pengaruh Penggunaan Media Video Animasi Interaktif Terhadap Hasil Belajar IPAS Siswa - Mega Putri, Nur Diana; Kharisma, Ahmad Ipmawan; Uswatun Khasanah, Linaria Arofatul Ilmi (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2025)
The Indonesian Ministry of Education and Culture changed the curriculum from the 2013 curriculum to the Independent Learning Curriculum. The term "independent learning" refers to a policy prepared by the government to improve the quality of education, which will ultimately create superior students and university students who are ready to face the very complex challenges of the future. The purpose of this study is to determine the effect of using interactive animated video media on the learning outcomes of fifth grade students at SDN Tambakrigadung II Lamongan. The method used was a quasi-experimental design. This research type is quantitative, and the design used in this study is a Nonequivalent Control Group Design. This study was conducted in the even semester. The sample in this study were fifth-grade students of SDN Tambakrigadung II Lamongan. Data collection techniques used were tests (pretest and posttest) and documentation. The results of this study showed that the average (mean) posttest score of students in the experimental class was 85.50 with a standard deviation of 1.850, while in the control class the average was 77.20 with a standard deviation of 2.142. This difference in averages indicates that students in the experimental class who used interactive animated video media achieved higher learning outcomes than students in the control class who did not use such media. The hypothesis calculation using a t-test obtained a significance level of 0.05. Because the significance value of 0.001, which is